SEKOLAH MODE ESMOD DI BANJARMASIN - Mintorwati, Mintorwati; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The Design of Fashion Schools in Banjarmasin is in the background by the rapid increase of fashion needs. Some potential young designers in Indonesia also show that fashion products in Indonesia have a great potential. However, in South Kalimantan, especially Banjarmasin, does not yet have a Fashion Design high school, it makes the local people who want to become a fashion designer must study outside the island of Kalimantan. With the existence of a fashion school in Banjarmasin, it is expected that Banjarmasin and the surrounding communities who have aspirations to become a Fashion Designer or want to know about what is Fashion Design. So, the fashion design school in Banjarmasin can give birth to new designers who can trigger the fashion industry in Indonesia, especially in Banjarmasin. In this design, the researcher uses the concept of Expressionist Architecture as an answer to the research problems in the design of this school.